Kualitas Layanan Publik, Transparansi, dan Akuntabilitas sebagai Faktor Penentu Kepercayaan Masyarakat - Azizah, Shofie; Kholifah Al Rosyadah, Hafidhoh; Yudha Pratama, Versiandika (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2024)
This study aims to determine the effect of public service quality, transparency, and accountability on public trust in the village government. This study uses a quantitative method with primary data sources obtained through distributing questionnaires to village communities in Batang Regency, and successfully obtained 100 respondents. Data analysis in this study was carried out using the multiple linear regression method with the help of SPSS software version 27. The results of this study indicate that the quality of public services has a significant effect on public trust in the village government. Likewise with the accountability variable, which shows a significant effect on public trust. However, the transparency variable does not have a significant effect on public trust. Meanwhile, when viewed together, the variables of public service quality, transparency, and accountability simultaneously affect public trust. This study emphasizes the importance of these three variables in building public trust in the village government. If the village government is able to provide good service, be transparent and accountable, the community will be more confident that the government is able to manage the village well. This will increase public trust in the village government.